2012
DOI: 10.1002/ccd.23365
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerotic inferior mesenteric artery stenosis resulting in large intestinal hypoperfusion: A paradigm shift in the diagnosis and management of symptomatic chronic mesenteric ischemia

Abstract: Symptomatic chronic mesenteric ischemia results from intestinal hypoperfusion and is classically thought to result from involvement of two or more mesenteric arteries. The celiac artery and superior mesenteric artery are most frequently implicated in this disease process, and their involvement usually results in symptoms of small intestinal ischemia. Symptomatic chronic mesenteric ischemia resulting predominantly from inferior mesenteric artery involvement has largely been overlooked but does gives rise to its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…However, after the occlusion of the IMA, a phenomenon of 'intestinal steal' occurred, with blood diverted for the IMA collateralization, causing small intestinal ischemia. It is indeed interesting to note that, judging by the scheme proposed by Lotun et al, 7 our patient's symptoms reflected small-bowel ischemia more than large-bowel ischemia despite relative patency of the CA and SMA.…”
Section: Discussionsupporting
confidence: 51%
“…However, after the occlusion of the IMA, a phenomenon of 'intestinal steal' occurred, with blood diverted for the IMA collateralization, causing small intestinal ischemia. It is indeed interesting to note that, judging by the scheme proposed by Lotun et al, 7 our patient's symptoms reflected small-bowel ischemia more than large-bowel ischemia despite relative patency of the CA and SMA.…”
Section: Discussionsupporting
confidence: 51%
“…Lotun et al described four patients with ischemia of the large intestine from isolated disease of the IMA who benefitted from percutaneous intervention of the IMA. 1 At the other extreme, there are patients with disease involving all three mesenteric arteries that remain asymptomatic. 2 The dilemma of equating an anatomic abnormality with clinical symptomatology becomes challenging.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of CCI , Lotun et al describe a series of four patients who presented with colonic ischemia, underwent percutaneous IMA revascularization, and enjoyed complete resolution of symptoms [3]. Of interest, these patients did not report classic symptoms of CMI such as post‐prandial abdominal pain and weight loss.…”
mentioning
confidence: 99%
“…Of importance, the authors observed that the splanchnic circulation in three of four patients was characterized by poor or absent contributions of the SMA to the marginal artery of Drummond, suggesting that the paucity of collateral communication may have predisposed the subjects to ischemia even in the presence of single‐vessel IMA stenosis. Informed by the presence of atypical CMI symptoms which were abolished by IMA revascularization, the authors propose a new classification scheme to stratify patients with CMI into small intestinal and large intestinal ischemia subgroups [3]. Patients with small intestinal ischemia are characterized by symptoms of sitophobia, postprandial abdominal pain, and weight loss—i.e.…”
mentioning
confidence: 99%